2006
DOI: 10.1080/j003v20n03_08
|View full text |Cite
|
Sign up to set email alerts
|

The After-School Occupations of Homeless Youth: Three Narrative Accounts

Abstract: SUMMARY This study describes the after-school and weekend time use of young adolescents residing in a temporary shelter for homeless families in Los Angeles County. Data were collected from three individual interviews, focus groups with 24 young adolescents and one-week time use journals. Data were analyzed qualitatively using the constant comparative method. Three narrative profiles were constructed from these data. Emergent themes and concepts describing the occupational participation of young adolescents du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 6 publications
2
4
0
Order By: Relevance
“…A number of studies targeted individuals who were misusing substances in the provision of either individual services that aim to promote occupational engagement or group-based activities. This finding is consistent with the emerging, mostly qualitative evidence identifying the occupational impact of substance use, the relationship between lack of occupational engagement and substance misuse, and engagement in pleasurable and meaningful activities as a way of occupying time that is typically used consuming substances (Amos et al, 1999; Cohen & Koegel, 1996; Marshall & Lysaght, 2014; McDonald, 2001; Raphael-Greenfield & Gutman, 2015).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…A number of studies targeted individuals who were misusing substances in the provision of either individual services that aim to promote occupational engagement or group-based activities. This finding is consistent with the emerging, mostly qualitative evidence identifying the occupational impact of substance use, the relationship between lack of occupational engagement and substance misuse, and engagement in pleasurable and meaningful activities as a way of occupying time that is typically used consuming substances (Amos et al, 1999; Cohen & Koegel, 1996; Marshall & Lysaght, 2014; McDonald, 2001; Raphael-Greenfield & Gutman, 2015).…”
Section: Discussionsupporting
confidence: 85%
“…One article described the role of an occupational therapist as an advocate within the field of homelessness (Marval & Townsend, 2013) through participating in a social media–based documentary. Eleven articles focused on the potential roles for occupational therapists in community building, particularly in advocacy, access to technology and online information on resources, outreach with this group of service users, discharge planning after hospital care, consultant work to design shelter and urban environments that promote occupational engagement, and involvement in policy making, program development, and evaluation at the level of organizations and cities (e.g., McDonald, 2006).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our preliminary findings build on existing evidence identifying boredom as a profound and pervasive experience with deleterious impacts on the mental and social well-being of homeless persons (McDonald, 2006; Marshall et al, 2017, 2018; Roy et al, 2017). They reveal a serious social injustice faced by this vulnerable population and are a call to action for researchers and practitioners alike.…”
Section: Discussionsupporting
confidence: 70%
“…Granted, on the surface, the issue of boredom seems like a trivial matter in light of the prevalence of mental and physical illness (Frankish, Hwang, & Quantz, 2005), trauma (Hopper, Bassuk, & Olivet, 2010), severe social exclusion (Shinn, 2010), and stigma (Benbow, Forchuk, & Ray, 2011) faced by this population. However, findings from recent research exploring related phenomena have revealed that boredom is a serious and pervasive experience for homeless persons and that its presence is reported to drive substance use and contribute to lowered mental well-being (Marshall, Lysaght, & Krupa, 2017, 2018; McDonald, 2006; Raphael-Greenfield & Gutman, 2015; Roy, Vallee, Kirsh, Marshall, Marval, & Low, 2017). To date, boredom has received little attention in existing literature related to homelessness.…”
mentioning
confidence: 99%